Environment control and risk assessment as COSO framework elements and their impact on the performance of entity: a case study in the Republic of Kosovo. (23rd June 2021) - Mjaku, Gresa; Bexheti, Abdylmenaf
This paper aims to investigate the impact of two elements of the COSO framework such as control environment and risk assessment on the performance of institutions of the Republic of Kosovo. We employ primary data due to lack of data by secondary data from other relevant institutions. The dataset includes a sample of 400 internal auditors. An IV-GMM model is implemented to measure the impact of two determinants in the public sector together with their metering instruments. Since the reliability of the data is proven, we think that this research has presented the current state of the institutions of the Republic of Kosovo and determining the main factors of the progress of this system. The results show that the control environment, including culture, transparency, structure, and human resource management have 73% impact on entity performance. Moreover, the results show that risk assessment as a second element of the COSO framework, including risk categorisation, identification, and risk reporting as measurement instruments of risk assessment. In the case of the Republic of Kosovo has an impact 24% in performance improvement in public entities.